Perilaku Menstrual Hygiene Management Yang Baik pada Remaja Putri dalam Menjaga Kebersihan Saat Menstruasi: Good Menstrual Hygiene Management Behavior in Adolescent Girls in Maintaining Cleanliness During Menstruation - Dyah Ayu Puspitasari; Natalia Devi Oktarina (Journal of Holistics and Health Sciences, 2026)
Menstrual Hygiene Management (MHM) is an important aspect of adolescent reproductive health, especially in early adolescence when adolescent girls begin to experience menstruation. Poor menstrual hygiene practices can increase the risk of reproductive tract infections. Based on the results of the preliminary study, MHM's behavior is still not good, because adolescent girls have not received information about MHM practices. The purpose of this study is to find out the description of menstrual hygiene management behavior in adolescent girls at Al-Mas'udiyyah Putri Junior High School. This study uses a quantitative method with a descriptive research design. Data collection was carried out through an observational method using a structured questionnaire consisting of 22 question items related to menstrual hygiene management. The population in this study is all adolescent girls in grade VII who have experienced menstruation at Al-Mas'udiyyah Junior High School Putri. The research sample amounted to 120 respondents with a total sampling technique. Data analysis was carried out univariate to describe the characteristics of respondents and menstrual hygiene management behavior. The results showed that most of the respondents were 12 years old, namely 76 respondents. Based on menstrual hygiene management behavior, as many as 73 respondents (60.8%) were in the good category. Most of the young women at Al-Mas'udiyyah Putri Junior High School have good menstrual hygiene management behavior. Young women are expected to improve correct menstrual hygiene management  behavior, especially in the use of underwear, the use of sanitary pads, and the hygiene of the body, skin, and hair.   ABSTRAK Menstrual Hygiene Management (MHM) merupakan aspek penting dalam kesehatan reproduksi remaja, khususnya pada masa awal remaja ketika remaja putri mulai mengalami menstruasi. Praktik kebersihan menstruasi yang kurang baik dapat meningkatkan risiko infeksi saluran reproduksi. Berdasarkan hasil studi pendahuluan, perilaku MHM masih kurang baik, karena remaja putri belum mendapat informasi tentang praktik MHM. Tujuan penelitian ini untuk mengetahui gambaran perilaku menstrual hygiene management pada remaja putri di SMP Al–Mas’udiyyah Putri. Penelitian ini menggunakan metode kuantitatif dengan desain penelitian deskriptif. Pengumpulan data dilakukan melalui metode lembar observasional menggunakan kuesioner terstruktur yang terdiri dari 22 item pertanyaan terkait menstrual hygiene management. Populasi dalam penelitian ini adalah seluruh remaja putri kelas VII yang telah mengalami menstruasi di SMP Al–Mas’udiyyah Putri. Sampel penelitian berjumlah 120 responden dengan teknik total sampling. Analisis data dilakukan secara univariat untuk menggambarkan karakteristik responden dan perilaku menstrual hygiene management. Hasil penelitian menunjukkan bahwa sebagian besar responden berusia 12 tahun, yaitu sebanyak 76 responden. Berdasarkan perilaku menstrual hygiene management, sebanyak 73 responden (60,8%) berada pada kategori baik. Sebagian besar remaja putri di SMP Al–Mas’udiyyah Putri memiliki perilaku menstrual hygiene management yang baik. Remaja putri diharapkan dapat meningkatkan perilaku menstrual hygiene management yang benar, khususnya dalam penggunaan pakaian dalam, penggunaan pembalut, dan kebersihan tubuh, kulit,dan rambut